Experimental measurements of the bacterial oxidation of HT in soils: Impact over a zone influenced by an industrial release of tritium in HT form. (February 2022) - Renard, H.; Connan, O.; Le Dizes, S.; Solier, L.; Hébert, D.; Cazimajou, O.; Laguionie, P.; D, Maro
Abstract: Tritium is a radionuclide released to the atmosphere by nuclear industries in various forms, mainly HTO and to a lesser extent HT. However, some nuclear sites may emit predominantly HT in the atmosphere. The HT is oxidized to HTO essentially in the top cm of soils, and that the formed HTO is then possibly released into the atmosphere. HTO is an assimilable form by plants. Therefore, it is important to understand the environmental behaviour of HT. In this work, we adapt the bacterial oxidation model of HT in soils of Ota et al. (2007) by laboratory experiments on soils typical of western France, and we have in particular adapted the frequency factor A and the Michaelis-Menten enzymatic reaction parameter (Km) on the basis of an Arrhenius equation in function of the porosity of the soil. We then applied this model to the environment near the reprocessing plant of Orano la Hague (France), which emits a significant amount of HT. Based on the adapted model, and knowing the atmospheric variations of HTO and HT over the period 2013–2016, we estimated that the mean HTO activity in soil due to atmospheric HT reached 0.6 Bq.L −1 (with a peak value of 5 Bq.L −1 ) while the mean value with all sources taken into account is 6.2 Bq.L −1 . Then, in an environment such as that surrounding the Orano La Hague plant, where near-field atmospheric HT activity is very high, the bacterial oxydation contribution to produce HTO in the soil can be considered as approximately 10%. The flux to the atmosphere from these source representing approximately. 1.5 Bq.m −2 .d −1 . If we consider an area of 2 km around the plant (i.e. 13 km 2 ), we estimate 218 Bq.s −1 of HTO was released by the soil, representing less than 0.1% of the direct atmospheric release of HTO around the site. From this work, it appears clear that this secondary source term from the soil is insignificant at this specific site. Highlights: Bacterial oxidation rate of HT in soils. Parametrization of oxidation in function of porosity of soils. Application to the release of HT from ORANO La Hague reprocessing plant.